Cancer multi-omics-based differential expression analysis and prognostic potential of identified hub targets of myco-metabolites for breast carcinoma and lung carcinoma - Singh Shreya; Debadatta Mohapatra; Gaurav Gopal Naik; Pooja Kathait; Soki Malang; Pradeep Patel; Shambhavi; Gulzar Alam; Alakh N. Sahu (Future Journal of Pharmaceutical Sciences)
Abstract Background Breast carcinoma (BC) and lung carcinoma (LC) have the highest incidence and mortality rates worldwide. In prior work, studied sample hub targets contributing to anticancer potential against BC and LC were identified through network pharmacology. In the present work, web servers UALCAN, GEPIA2, and KM plotter were used to explore the genomic and proteomic expression of these hub targets, along with their prognosis potential in BC and LC. Results Differential hub targets SRC, MAPK3, PTPN11, JAK2, ESR1, and HAP900A1 for BC and PTPN11, JAK2, ESR1, EGFR, and MAPK3 for LC, showed good prognostic potentials. Collectively, PTPN11, JAK2, and ESR1 were overlapped differential expressed hub targets involved in the significantly good prognosis of both carcinoma. Conclusion These differentially expressed hub targets may be taken into account for future BC and LC treatments due to their strong prognostic potential.